Legal Support of the Process of Kazakhstan Accession to the OECD: Potential for Improving Quality of Individual's Labour Rights Regulation - ZHETPISBAYEV, Batyrbek A.; BAISALOVA, Gulzira T.; SHADIYEV, Kairatbek Kh.; KHAMZIN, Amangeldy Sh.; BURIBAYEV, Yermek A.; KHAMZINA, Zhanna A. (Journal of Advanced Research in Law and Economics, 2017)
The leading concept of the research is to prepare, implement scientific and practical recommendations, proposals aimed at improving the quality of legal regulation of wage employment in Kazakhstan. The study has two interrelated end goals: the development of a scientific and legal basis for Kazakhstan's accession to the Organization for Economic Cooperation and Development (OECD, Organization) and the unification of the national Labour legislation with universally recognized standards for the implementation of Labour relations in OECD countries.The aim is to theoretically substantiate the concept and content of the legal framework for ensuring human rights in the OECD countries; to generalize and develop ideas for solving the issues of improving the quality of legal regulation of the social and Labour sphere in Kazakhstan; to investigate problems and suggest ways of transforming the standards of wage Labour recognized in OECD countries into the Kazakhstani system of law.As a result of the research, conclusions and proposals are formulated aimed at improving and modernizing the norms of the Labour legislation of the Republic of Kazakhstan in the context of the development of all spheres of public administration and regulation in accordance with OECD recommendations and standards.